Thomism and Atheism - Schall, James V. (New blackfriars, 2011)
Atheism, the thesis that God does not exist and Thomism, the thesis that there are “proofs” for the existence of God based on experience and reason can be juxtaposed to each other as two extremes. On the other hand, the very statement of each implies the need to consider the other, so that the atheist and the Thomist both claim to belong to rational discourse, however much they differ in conclusions. The scriptural tradition has consistently found the one who says there is “no God” to be “foolish,” that is, someone with more than just an intellectual error.